2018
DOI: 10.38004/sobad.480851
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrenci̇leri̇ni̇n Beden Eği̇ti̇mi̇ Dersi̇ne Yöneli̇k Tutumlarinin İncelenmesi̇

Abstract: Araştırmanın amacı, ortaokul öğrencilerinin farklı değişkenler açısından beden eğitimi dersine yönelik tutumlarının incelenmesidir. Araştırma örneklemini, Osmaniye ilinde taşra ve merkez dahil olmak üzere 2016-2017 eğitim-öğretim yılı içerisinde 9 devlet orta okulunda öğrenim görmekte olan 1837 (erkek 890 kız 947) ortaokul öğrencisi oluşturmuştur. Araştırmada veri toplama aracı olarak Güllü ve Güçlü (2009) yılında geliştirilen "Beden Eğitimi Dersi Tutum Ölçeği" kullanılmıştır. Ölçek, 24 maddesi olumlu ve 11 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is also a known fact that male students' participation in physical education classes is high (Yıldız & Özgül, 2017). Male students with high participation in lesson activities had more positive lesson attitudes compared to female students (Cengiz et al, 2018;Kumar & Singh, 2011). Today, female students' participation in sports has increased significantly.…”
Section: Physical Education Lesson Attitude and Gendermentioning
confidence: 99%
“…It is also a known fact that male students' participation in physical education classes is high (Yıldız & Özgül, 2017). Male students with high participation in lesson activities had more positive lesson attitudes compared to female students (Cengiz et al, 2018;Kumar & Singh, 2011). Today, female students' participation in sports has increased significantly.…”
Section: Physical Education Lesson Attitude and Gendermentioning
confidence: 99%
“…In the study conducted by Doğan (2011, p.37) on high school students, it was stated that the attitudes of students studying in different high schools to physical education and sports lessons did not differ according to gender. In the literature, there are studies stating that male students have high participation in physical education and sports lessons (Lazarevic et al, 2015;Cengiz et al, 2018). In the study conducted by Ekici et al (2011, p.837) on students studying in high schools, it was found that students' attitudes towards physical education and sports lessons differ significantly according to their grade levels.…”
Section: Investigation Of Thementioning
confidence: 99%